Identity Discourses and Canadian Foreign Policy in the War on Terror - McDonald, Taylor Robertson (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book examines how popular narratives of Canadian identity became implicated in Canada's foreign policy in the Global War on Terror. McDonald argues that Canada's decisions to join the 2001 Afghanistan War yet abstain from the 2003 Iraq War became politically possible because parliamentarians linked these policies to similar narratives of an enduring Canadian identity - even while re-imagining their meanings. These decisions are explored through politicians' mobilization of three discourses: Canada as America's neighbour, Canada as protector of foreign civilians, and Canada as a champion of multilateralism. This book challenges conceptions of national identity as entirely stable or fluid and contests predominant arguments that downplay the role of identity discourses in Canadian foreign policy. The relevance of these narratives is assessed by exploring the rhetoric of Canadian foreign policy in light of contemporary international challenges, including the Donald Trump presidency, the COVID-19 pandemic, and Russia's War on Ukraine. Dr. Taylor Robertson McDonald is a Scholar-in-residence at American University's School of International Service in Washington, D.C. He is a former post-doctoral fellow at the Taube Centre for Advanced Studies in the Social Sciences at The Jagiellonian University in Kraków, Poland.
Chapter 1: Introduction -- Chapter 2: Identity and Foreign Policy as Discursive Practices: A Framework -- Chapter 3: Won't You Be My Neighbour? Discourses of Canada's "Neighbourly Relations" and the War on Terror -- Chapter 4: Crusading Saviour and Condemning Onlooker: Discourses of Canada the Protector and the War on Terror -- Chapter 5: All for One, One for All: Discourses of Canadian Multilateralism and the War on Terror -- Chapter 6: Reimagining Canada? Foreign Policy Discourses in the Age of Trump, Putin and Pandemic Politics -- Chapter 7: Conclusion. .
Keywords: International relations; Middle East -- Politics and government; International Relations Theory; Foreign Policy; Middle Eastern Politics